2016
DOI: 10.1111/jir.12278
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of psychiatric diagnoses and maladaptive behaviour in youth with severe developmental disability

Abstract: Youth with severe and profound ID who experience psychosocial stressors are more likely reported to have mental health problems than youth without such stressors. It is likely that a combination of child and family based interventions, along with with policies that address larger systemic issues of social adversity, are needed to promote mental health and treat psychopathology when it arises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…There are some studies that specifically address QoL in families with severe to profound intellectual disabilities (Chou, Chiao, & Fu, 2011;Schertz, Karni-Visel, Tamir, Genizi, & Roth, 2016;Weiss, Ting, & Perry, 2016), and the degree of intellectual disabilities seems to play an important role in FQoL as a predictor of family well-being (Chou et al, 2011;Hu, Wang, & Fei, 2012;Wang et al, 2004).…”
mentioning
confidence: 99%
“…There are some studies that specifically address QoL in families with severe to profound intellectual disabilities (Chou, Chiao, & Fu, 2011;Schertz, Karni-Visel, Tamir, Genizi, & Roth, 2016;Weiss, Ting, & Perry, 2016), and the degree of intellectual disabilities seems to play an important role in FQoL as a predictor of family well-being (Chou et al, 2011;Hu, Wang, & Fei, 2012;Wang et al, 2004).…”
mentioning
confidence: 99%
“…Several authors have found a significant relationship between ID and an increased incidence of behavioural problems (Ahuja, Martin, Langley, & Thapar, ; Embregts, du Bois, & Graef, ; Myrbakk & von Tetzchnner, ; Weiss, Ting, & Perry, ) and anxiety (Reardon, Gray, & Melvin, ). On the other hand, children with ID were found to use illegal drugs at a lower rate than those without disability, but were more vulnerable to problems arising from substance use (Carroll Chapman, & Wu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with developmental disabilities frequently require behavioral intervention, with researchers estimating that 48% to 82% of individuals with developmental disabilities exhibit problem behavior (Lecavalier, 2006;Poppes, van der Putten, & Vlaskamp, 2010;Rojahn, Matson, Lott, Esbensen, & Smalls, 2001). More recently, Weiss, Ting, and Perry (2016) found that 40.4% of a sample of children with severe developmental disabilities, including ASD, exhibited serious maladaptive behavior. Common problem behaviors observed in school settings include temper tantrums, arguing, and defiance, with behaviors such as self-injury and refusing to talk occurring in a substantial number of individuals (Lecavalier, 2006).…”
mentioning
confidence: 99%